In Everything I See Your Hand - Kuzmich, Naira (Book collections on Project MUSE., 2022)
"What's the difference between leaving the motherland and leaving the literal mother? When does the journey toward self-possession become something closer to self-exile? Living daily in the tension between assimilation, disillusionment, and desire, the Armenian-American protagonists of In Everything I See Your Hand struggle with the belief that their futures are already decided, futures that can only be escaped through death or departure-if they can be escaped at all. In these ten brilliant stories, Naira Kuzmich spins variations of immigrant life in the Little Armenia neighborhood of Los Angeles. Kuzmich finished this collection before her death at age twenty-nine. Melding empathy, savvy, and candor through ardently wrought language, these stories are gifts that seduce, devastate, and shine"--